Analysis of labor costs and efficiency of labor resources utilization ("Journal "U". Economy. Management. Finance.", 2024)
In the framework of this study the author considered the methods of labor cost analysis and efficiency of labor resources use. The main stages of the analysis of labor costs are highlighted. Methods of optimization of labor costs are developed. The methods of increasing labor productivity at the enterprise are highlighted. The practical significance of the work is that the results obtained in the study can be applied in order to solve existing problems.
Keywords: analysis; efficiency; enterprise; wages; labor resources; employees